2019
DOI: 10.1002/pmrj.12173
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to a Motor Vehicle Collision and the Risk of Future Neck Pain: A Systematic Review and Meta‐Analysis

Abstract: ObjectiveTo summarize the literature that has examined the association between a motor vehicle collision (MVC) related neck injury and future neck pain (NP) in comparison with the population that has not been exposed to neck injury from an MVC.Literature SurveyNeck injury resulting from an MVC is associated with a high rate of chronicity. Prognosis studies indicate 50% of injured people continue to experience NP a year after the collision. This is difficult to interpret due to the high prevalence of NP in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 39 publications
0
10
0
1
Order By: Relevance
“…Whiplash is a common injury following road traffic crashes affecting several million people worldwide each year. A significant proportion, up to 50%, develop chronic/long-term symptoms [ 1 3 ] and approximately 15% of those initially injured suffer from reduced working capability due to ongoing disability [ 3 ]. Chronic whiplash patients often complain of neck pain, headaches and pain in the cervico-thoracic region of the spine.…”
Section: Introductionmentioning
confidence: 99%
“…Whiplash is a common injury following road traffic crashes affecting several million people worldwide each year. A significant proportion, up to 50%, develop chronic/long-term symptoms [ 1 3 ] and approximately 15% of those initially injured suffer from reduced working capability due to ongoing disability [ 3 ]. Chronic whiplash patients often complain of neck pain, headaches and pain in the cervico-thoracic region of the spine.…”
Section: Introductionmentioning
confidence: 99%
“…After a TA, various musculoskeletal injuries, internal bruises, and psychological trauma may result, [ 9 , 10 ] while common symptoms after a TA often include neck pain or LBP. [ 11 , 12 ] One study reported that approximately 37% of patients complained of severe LBP only 6 weeks after a TA and 23% of cases involved both neck and LBP. [ 9 ] Another cohort study reported that 60.4% of patients who were treated within 30 days of an accident complained of LBP.…”
Section: Introductionmentioning
confidence: 99%
“…NP is common after an injury in a motor vehicle collision (MVC) with 86% of individuals reporting neck pain, and with the pain still occurring in 50% of those individuals a year later [5,6]. In a systematic review and meta-analysis of six studies with individuals who had sustained a neck injury in a MVC, those with neck injuries were at a greater risk of future neck pain when compared to those without a neck injury (RR = 2.3 [95% CI 1.8-3.1]) [7]. Cervical pain can have multiple etiologies, including cervical dystonia, instability, protrusion, and ligamentous damage.…”
Section: Introductionmentioning
confidence: 99%